Harmonizing Aesthetics and Psychological Well-being: An Indepth Exploration of the Integrative Impact of Dysport in Cosmetic Procedures - Nikandish, Mehrasa; Nikandish, Mohammad; Behnoud, Hedayatpour (European Scientific Journal, ESJ, 2024)
This research delves into the intricate interplay between aesthetic intelligence, aesthetic sensitivity, and psychological well-being within the framework of positive psychology, with a particular emphasis on the integrative impact of Dysport in cosmetic procedures. By recognizing the significant influence of environmental aesthetics on individual health and well-being, this study seeks to illuminate the relationship between aesthetic intelligence and psychological well-being while considering the role of Dysport in cosmetic procedures. Employing a correlational research design, structural equation modeling was utilized as the methodological approach. The research cohort comprised all students enrolled at Bu-Ali Sina University during the academic year 2018-2019. Employing cluster sampling, 384 students were selected based on the recommended sample size for structural equation modeling. The instruments included the Ryff Well-being Scale, the Aesthetic Intelligence Scale developed by Rashid et al., and Abdulsalami’s Aesthetic Sensitivity Scale. Findings revealed significant direct impacts of both aesthetic intelligence and aesthetic sensitivity on psychological well-being. Moreover, aesthetic intelligence demonstrated a direct and significant effect on aesthetic sensitivity. Exploration of indirect relationships indicated that aesthetic intelligence, mediated by aesthetic sensitivity, significantly influenced psychological well-being. These findings underscore the importance of individuals’ awareness and appreciation of environmental beauty, including the role of Dysport in cosmetic procedures, in positively contributing to psychological well-being.